Peningkatan Kemampuan Berpikir Kritis Menggunakan Model Problem Based Learning (PBL) pada Tematik Terpadu - Sadi, Rike Permata; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2016)
The research is caused by low outcomes of critical thinking skills of students. The purpose of this research was to describe the improvement of critical thinking skills using the Problem Based Learning (PBL) model on the integrated thematic class IV SDN 03 Feed Labuah Bukittinggi City. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. The research subjects were the fourth grade students of SDN 03 Feed Labuah, Bukittinggi City, amounting to 25 people. The study was conducted in two cycles. The results showed an increase in the average observation results of RPP cycle I was 73.60% (C) increased in the second cycle to 94.44% (AB), this is also seen in the average results of the implementation of learning aspects of the teacher cycle I was 74 , 99% (C) increases in cycle II to 95% (AB). On the aspects of students, the average cycle I was 71.66% (C) increased in the second cycle to 93.33% (AB). While the average assessment of students' critical thinking skills in the first cycle was 61.68% (C) and increased in the second cycle, 83.45 (A-). Thus the Problem Based Learning (PBL) model can improve critical thinking skills in the integrated thematic class IV students of SDN 03 Feed Labuah, Bukittinggi City.